Analysis of Credit Provision to PD. BPR Bahteramas Baubau - Ahmad Saiful (AIQU: Journal Multidiscipliner of Science, 2024)
PD. BPR Bahteramas Baubau is a bank that is quite popular with customers to apply for credit. The internal control system is supervised by a supervisory section consisting of one person who supervises the internal control in the company. The Internal Control System in PD. BPR Bahteramas Baubau is already very good because it has a clear organizational structure and a good division of employee tasks according to the abilities of each employee. The objectives to be achieved in this study are to analyze internal control and credit provision at PD. BPR Bahteramas Baubau. The analysis tool used in this study is a qualitative method and the samples used are observation, interviews and documentation. Based on the results obtained, the provision of credit at PD. BPR Bahteramas Baubau has fully implemented the 5C principle and is in accordance with Syafril's theory. This is done to meet the terms and conditions that apply to prospective customers in applying for credit so that there is no credit congestion consisting of: character, capacity, collateral, capital, condition.